Sources of financing and factors hindering the development of innovative activities of the sphere of tourism - Karimova Aziza Mahommadrezaevna (Universitas Muhammadiyah Sidoarjo, 2020)
This article discusses the role of the tourism industry in the development of the country's economy, factors hindering its development, as well as problems associated with sources of financing for this activity. Despite the fact that today tourism has turned into one of the most promising areas, there are many problems that both legal entities and individuals face. The article provides suggestions, the implementation of which would contribute to the solution of existing problems.